2010
DOI: 10.1111/j.1600-0587.2009.06000.x
|View full text |Cite
|
Sign up to set email alerts
|

BioMove – an integrated platform simulating the dynamic response of species to environmental change

Abstract: BioMove simulates plant species' geographic range shifts in response to climate, habitat structure and disturbance, at annual time steps. This spatially explicit approach integrates species' bioclimatic suitability and population-level demographic rates with simulation of landscape-level processes (dispersal, disturbance, species' response to dynamic dominant vegetation structure). Species population dynamics are simulated through matrix modelling that includes scaling demographic rates by climatic suitability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
99
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(101 citation statements)
references
References 14 publications
0
99
0
2
Order By: Relevance
“…As many indicator-species approaches, particularly the MCR method, place major emphasis on the range limits of species rather than the probability of occurrence within their range, understanding the dynamics of range limits in relation to climate is critical (Gaston 2009;Pigot et al 2010). Recently, Keith et al (2008), Anderson et al (2009), Buckley et al (2010), and Huntley et al (2010) have shown the importance and feasibility of moving from simple bioclimatic-envelope models to models that incorporate dynamic climate change and metapopulation dynamics (see also Jackson et al 2009 andMidgley et al 2010). Palaeoecologists using bioclimate-envelope approaches to reconstruct past climate from fossil assemblages could profitably test the robustness of their correlative methods by applying appropriate statistical tests to establish if the distribution of the taxa used in climate reconstructions show statistical relationships with climate, along the lines of Beale et al (2008) and Chapman (2010.…”
Section: Strengths and Weaknessesmentioning
confidence: 99%
“…As many indicator-species approaches, particularly the MCR method, place major emphasis on the range limits of species rather than the probability of occurrence within their range, understanding the dynamics of range limits in relation to climate is critical (Gaston 2009;Pigot et al 2010). Recently, Keith et al (2008), Anderson et al (2009), Buckley et al (2010), and Huntley et al (2010) have shown the importance and feasibility of moving from simple bioclimatic-envelope models to models that incorporate dynamic climate change and metapopulation dynamics (see also Jackson et al 2009 andMidgley et al 2010). Palaeoecologists using bioclimate-envelope approaches to reconstruct past climate from fossil assemblages could profitably test the robustness of their correlative methods by applying appropriate statistical tests to establish if the distribution of the taxa used in climate reconstructions show statistical relationships with climate, along the lines of Beale et al (2008) and Chapman (2010.…”
Section: Strengths and Weaknessesmentioning
confidence: 99%
“…Accordingly, the importance of studies considering other factors has been emphasized (Guisan and Thuiller, 2005;Elith and Leathwick 2009). In particular, dispersal is an important mechanism to understand how plants adapt to climate changes; as a result, related models, such as Migclim and Biomove, have been developed and applied to the predictions of future plant distributions under climate change Midgley et al 2010;Engler et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, demographic models are very rare in SDM studies due to the paucity of comparable abundance data, and subsequently have only been applied in a few studies (e.g. Midgley et al 2010). As such, it was not practical to include these conceptualizations of dispersal in the analysis.…”
Section: Discussionmentioning
confidence: 99%